Pineal melatonin acts as a circadian zeitgeber and growth factor in chick astrocytes - Paulose, Jiffin K. (2009)
Melatonin is rhythmically synthesized and released by the avian pineal gland and retina during the night, targeting an array of tissues and affecting a variety of physiological and behavioral processes. Among these targets, astrocytes express two melatonin receptor subtypes in vitro, the Mel(1A) and Mel(1C) receptors, which play a role in regulating metabolic activity and calcium homeostasis in these cells. Molecular characterization of chick astrocytes has revealed the expression of orthologs of the mammalian clock genes including clock, cry1, cry2, per2, and per3. To test the hypothesis that pineal melatonin entrains molecular clockworks in downstream cells, we asked whether coculturing astrocytes with pinealocytes or administration of exogenous melatonin cycles would entrain metabolic rhythms of 2-deoxy [14C]-glucose (2DG] uptake and/or clock gene expression in cultured astrocytes. Rhythmic secretion of melatonin from light-entrained pinealocytes in coculture as well as cyclic administration of exogenous melatonin entrained rhythms of 2DG uptake and expression of Gallus per2 (gper2) and/or gper3, but not of gcry1 mRNA. Surprisingly, melatonin also caused a dose-dependent increase in mitotic activity of astrocytes, both in coculture and when administered exogenously. The observation that melatonin stimulates mitotic activity in diencephalic astrocytes suggests a trophic role of the hormone in brain development. The data suggest a dual role for melatonin in avian astrocytes: synchronization of rhythmic processes in these cells and regulation of growth and differentiation. These two processes may or may not be mutually exclusive.